A Drone-Based Approach for Radiometric Mapping of Gamma Radiation - Felipe Mamed; Alessandra Vaz; Ary Machado; Joana Batista; Jonathan Oliveira; Paulo Silveira; Paulo Iack; Paulo Barreto; William Henrique; Wallace Vallory (Brazilian Journal of Radiation Sciences, 2025)
This work presents the results of an experiment conducted with an Unmanned Aerial Vehicle (UAV) equipped with a Geiger-Müller detector module, aimed at validating a gamma radiation detection methodology. The experiment took place at the Batalhão Central de Manutenção e Suprimentos (BCMS) in Rio de Janeiro, where a Cesium-137 source was positioned at a specific point within a designated area for the drone flight. The measurement methodology involves continuous flight, with point-by-point readings taken at designated locations. Subsequently, during the data processing stage, each measurement point was organized into cells, forming a structured grid that served as the basis for generating a three-dimensional map of gamma radiation dose distribution. After processing the data collected by the drone, a dose profile was reconstructed, allowing for a satisfactory estimation of the location where the Cesium-137 source was positioned based on the radiation peak. Since specific patterns in the graphs, such as a sudden increase in dose rate in a particular direction, can indicate the presence of a source, we consider that this method can be employed as a useful strategy for the remote detection of radiation sources in various environments, offering a satisfactory approximation of the radiological conditions present in the analyzed environment.